La duplicación de funciones y posiciones de parentesco como estrategia para la construcción de la paternidad/maternidad en las familias reconstituidas - Jociles Rubio, María Isabel (2008)
It is interesting to notice that authors such as Théry (1985), le Gall and Marin (1993) and le Gall (1996) who study reconstituted families have not dealt with all of the possible consequences of the idea of family constellation, specially the one which states that the concept of family should include more than just residency. Another point to notice is that the paternity and maternity analysis hasn’t been applied within the family modality. This article presents the results of an investigation where this idea has proven to be very successful in analysing the ways in which father/mother and stepfather/stepmother parental positions and roles are formed in the basis of these families, given that the ways in which the role or parental position of a biological father without custody is formed is not independent from other ways in which a stepfather manages to build his parental position, just like during these processes members of the family constellation also have some influence, such as the spouses’s or couple’s parents.